Beyond the ivory tower : international relations theory and the issue of policy relevance - Lepgold, Joseph (Columbia international affairs online. Books., 2001)
The gap between academics and practitioners in international relations has widened in recent years, according to the authors of this book. Globalization, ethnic conflict, and ecological threats have created a new set of issues that challenge policymakers, and cutting-edge scholarship can contribute a great deal to the diagnosis and handling of potentially explosive situations.